An Analysis of Phonological Mistake in the YouTube “Vior dan Vincent Bertemu Satpam GI” on Raditya Dika Channel - Diana Tri Widarti; Martius Martius; Rina Fitriani; Vera Sardila; Welli Marlisa (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study aims to describe the pronunciation mitake in Youtube “Vior dan Vincent Bertemu Satpam GI”. Data were collected using the listening and note-taking methods, then analyzed using insertion, deletion, and replacement techniques. Furthermore, the following conclusions were obtained: (1) mistake in the form of phoneme changes, consisting of (a) vowel pronunciation mistake, (b) consonant pronunciation mistakes, (2) mistake due to phoneme omissions consisting of (a) omission of the phoneme /h/ in the onsed and coda positions, (b) omission of the phoneme /s/ in the consoant cluster /ks/, and omission of the phoneme /k/ in the consonant cluster /ks/; (3) mistake in the form of added phonemes, namely the addition of the phoneme /n/ in the nucleus position of the word.